La Collezione Peggy Guggenheim. - Barr, Alfred H. Jr.; Read, Herbert; Sandberg, Willem (Venezia : Peggy Guggenheim Collection)
Admiral, Virginia ; Appel, Karel ; Archipenko, Alexander ; Armitage, Kenneth ; Arp, Hans (Jean) ; Bacci, Edmondo ; Bacon, Francis ; Balla, Giacomo ; Baziotes, William ; Boccioni, Umberto ; Brancusi, Constantin ; Braque, Georges ; Brauner, Victor ; Buggiani, Paolo ; Butler, Reg ; Calder, Alexander ; Campigli, Massimo ; Consagra, Pietro ; César ; Chadwick, Lynn ; Chagall, Marc ; De Chirico, Giorgio ; Cocteau, Jean ; Congdon, William ; Dali, Salvador ; Davie, Alan ; Delaunay, Robert ; Delvaux, Paul ; van Doesburg, Theo ; Duchamp, Marcel ; Duchamp-Villon, Raymond ; Ernst, Max ; Ferren, John ; Fini, Leonor ; Garelli, Franco ; Giacometti, Alberto ; Gleizes, Albert ; Gonzales, Julio ; Gorky, Arshile ; Gris, Juan ; Hare, David ; Hartung, Hans ; Hayter, Stanley William ; Hélion, Jean ; Hirschfield, Morris ; Irwin, Gwther ; Jenkins, Paul ; Kandinsky, Wassily ; Klee, Paul ; Koenig, Fritz ; Lardera, Berto ; Leger, Fernand ; Lipchitz, Jacques ; Lissitzky, El ; Magritte, René ; Malevich, Kasimir ; Man Ray ; Marcoussis, Louis ; Marini, Marino ; Masson, Andre ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Metzinger, Jean ; Minguzzi, Luciano ; Mirko ; Miro, Joan ; Mondriaan, Piet ; Moore, Henry ; Motherwell, Robert ; Nicholson, Ben ; Ozenfant, Amédée ; Pegeen ; Pevsner, Antoine ; Picabia, Francis ; Picasso, Pablo ; Pirandello, Fausto ; Pollock, Jackson ; Prampolini, Enrico ; Rothko, Mark ; Scalini, Giuditta ; Schwitters, Kurt ; Scott, Kenneth ; Severini, Gino ; Sobel, Janet ; Still, Clyfford ; Takis ; Tancredi ; Tanguy, Yves ; Thornton, Leslie Tillotson ; Van Tongerloo, Georges ; Tunnard, John ; Vail, Lawrence ; Vedova, Emilio ; Villon, Jacques ; Yacoubi, Ahmed ; Yorn, Asger
Biog. per kunstenaar
La Collezione Peggy Guggenheim e visible a Palazzo Venier dei Leoni, Venezia
Italiaans & Engels & Frans
boek